COMPARATIVE ANALYSIS OF THE LEXICON OF "ETIQUETTE" IN ENGLISH AND UZBEK - Hatamova Yulduz Raxmatulla qizi; Uralova Oysuluv Poyan qizi (Western European Studies, 2025)
This paper presents a comparative analysis of the lexicon of “etiquette” in English and Uzbek, focusing on how cultural norms shape linguistic expressions of politeness. Using a qualitative method based on dictionary sources, literary texts, and real-life discourse, the study identifies key lexical items and strategies used in both languages to express politeness, respect, and social hierarchy. While English etiquette emphasizes clarity, individual autonomy, and indirectness through modal verbs, Uzbek etiquette highlights social harmony, age-based respect, and elaborate euphemisms. Drawing on theories of politeness by Brown & Levinson and cultural linguistics, the research finds that although the communicative goal is shared, the lexical realization differs significantly due to contrasting cultural values. The paper concludes that a deeper understanding of these differences is essential for successful crosscultural communication and for avoiding pragmatic failure in intercultural interactions.
Keywords: etiquette; lexicon; Uzbek